FLUPIRTINE: A MINI REVIEW - kumar, raj; Keshri, Umashanker Prasad; Sharma, Janardan (Journal of Drug Delivery and Therapeutics, 2013)
Pain is the oldest medical problem of human, yet it has been little understood in physiology until very recently. Persistent, unremitting pain may adversely affect the bodyâ€™s endocrine, cardiovascular, immune, neurologic and musculo-skeletal systems and require aggressive treatment of the pain as well as its complications. It can significantly interfere with a person's quality of life and general functioning. So, treatment of this sensation is a challenge for clinicians. Flupirtine is a novel, centrally acting, non-opioid and non NSAID analgesic agent, and is devoid of common adverse effects seen with NSAIDs and opioids. It was first synthesized and used in Europe although it is not yet approved by United States Food and Drug Administration (USFDA). It acts as a selective neuronal potassium channel opener and has indirect N-methyl-d-aspartate (NMDA) receptor antagonist properties. In addition to analgesic action, it has also muscle relaxant, antioxidant, neuroprotective and antiparkinsonian effects. It is presently under phase II clinical trials for fibromyalgia. Evidence of flupirtine's efficacy from clinical trials and well-established use in European countries for more than 25 years suggests that it has a unique and important place in pain management. Despite its broad spectrum action, it is among such drugs which were not popular worldwide for a long time becauseÂ  they were not approved by USFDA. Key Words: Pain, Flupirtine, Selective neuronal potassium channel openers, Neuroprotective, Antioxidant.